The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3329/bjvm.v11i1.17730
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of reproductive and production diseases of cross-bred dairy cattle in Bangladesh

Abstract: Reproductive and production disorders (PD) of cross-bred dairy cattle significantly reduce their productivity which is of great concern of dairy producers worldwide because most reproductive disorders adversely affect the future fertility. The present study was conducted to determine the incidence of some reproductive diseases (RD) like abortion, anoestrus, metritis, repeat breeder, retained placenta and one production disease like clinical mastitis in cross-bred dairy cattle in Shahjadpur upazila of Sirajgonj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
(15 reference statements)
6
14
2
Order By: Relevance
“…Repeat breeder (17.10%), retained placenta (14.27%) and anestrous (11.44%) were most common reproductive diseases. Khair et al (2013) also observed higher occurrence of these diseases in the same area. Our clinical experience and opinion from field veterinarian are also in agreement with the findings of this study.…”
Section: Production and Reproductive Disorderssupporting
confidence: 51%
“…Repeat breeder (17.10%), retained placenta (14.27%) and anestrous (11.44%) were most common reproductive diseases. Khair et al (2013) also observed higher occurrence of these diseases in the same area. Our clinical experience and opinion from field veterinarian are also in agreement with the findings of this study.…”
Section: Production and Reproductive Disorderssupporting
confidence: 51%
“…Therewith, many previous studies reported that the incidence of dystocia is 6.9% in cattle [3,14] and buffaloes (0.70-6.3) % in buffaloes [15] which is coincide with our observation. This study showed that the occurrence of reproductive cases commonly occurred in cross breeds (31.6-87.5) % which is supported by [16,17,18]. The proportionate prevalence of reproductive cases in older animals (42.1-87.5) % with higher parity (31-87.5)% was higher in this study, is agreed with many studies [19,20].…”
Section: Discussionsupporting
confidence: 82%
“…Similarly the general frequency of the disease was randomly distributed throughout the year, but relatively more cases were encountered during the month of July to October (rainy season) followed by month of November to February (winter season) than the month of March to June (dry or summer season) which partially agree with Khair et al [21] (2013) and disagree with Waziri et al [15] (2006) The rainy season lies highest frequency may be due to the lack or scarcity of fodder and lack of grazing. …”
Section: Discussionsupporting
confidence: 80%